2022
DOI: 10.1002/vjch.202200080
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of organic titanate modified titanium dioxide nanoparticles and its dispersibility in acrylic emulsion coating

Nguyen Thuy Chinh,
Tran Thi Mai,
Dao Phi Hung
et al.

Abstract: This work presents the characteristics of rutile TiO2 nanoparticles modified by isopropyl tri[di(octyl) phosphato] titanate (KR‐12) with the content of 3, 5 and 10 wt.% as compared to TiO2 nanoparticles weight. The infrared (IR) spectroscopy, scanning electron microscopy (SEM), dynamic light scattering (DLS), and thermal gravimetry analysis (TGA) methods were used to evaluate the surface modification efficiency of the TiO2 nanoparticles with KR‐12. The TGA and IR analysis results indicated that the organic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As can be seen, an increase in the calcination temperature from 300 to 800 °C significantly decreases the bandgap energy of the material from 2.91 to 1.78 eV, which can be ascribed to the gradual generation of the rutile phase during the calcination process. It has been reported that the bandgap energy of pristine TiO 2 is approximately 3 eV based on diverse synthesis procedures, , which is higher than those of all MFO-TiO 2 samples. This phenomenon can be assigned to the participation of the ferrite nanostructure with low band gap energy as well as the support of the polymer matrix of chitosan, which is responsible for the good crystallinity and stability of the MFO-TiO 2 , thanks to the strong interaction with long-chain carbohydrate.…”
Section: Resultsmentioning
confidence: 89%
“…As can be seen, an increase in the calcination temperature from 300 to 800 °C significantly decreases the bandgap energy of the material from 2.91 to 1.78 eV, which can be ascribed to the gradual generation of the rutile phase during the calcination process. It has been reported that the bandgap energy of pristine TiO 2 is approximately 3 eV based on diverse synthesis procedures, , which is higher than those of all MFO-TiO 2 samples. This phenomenon can be assigned to the participation of the ferrite nanostructure with low band gap energy as well as the support of the polymer matrix of chitosan, which is responsible for the good crystallinity and stability of the MFO-TiO 2 , thanks to the strong interaction with long-chain carbohydrate.…”
Section: Resultsmentioning
confidence: 89%